Length-weight relationship, condition factor, and distribution of spotted barb (Barbodes binotatus Valenciennes, 1842) in Lake Tamblingan Bali - Nyoman Dati Pertami; I Nyoman Yoga Parawangsa (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2021)
Tamblingan Lake is a volcanic lake located in the caldera of Mount Lesung a rain-fed lake in a confined endorheic basin and there is no inflow or outflow. Nyalian is a type of fish from the Cyprinidae family that is quite common compared to other fish in its class in Tamblingan Lake. Information on the growth and distribution of these fish parameters in Tamblingan Lake does not exist. This study aims to analyze and explain the growth patterns of Barbodes binotatus, especially the length-weight relationship, condition factor, and their distribution in the waters of Tamblingan Lake. The research was conducted in Tamblingan Lake from January to June 2019 using a modify gill nets with the mesh size 0.5; 1.0; 1.5; 2.0; 2.5; 3.0 in centimeter. The sampling done in five locations. The length-weight relationship analysis used the power regression. The fish sample found was 204 individuals during the study with a range of total length was 5.2 – 15.0 cm. The equation of length-weight relationship is W = 0.0051 L3.387. The value of b formed based on this equation is 3.387 with a positive allometric growth pattern.The condition factor values ranged from 0.587 to 1.246. Barbodes binotatus spread in the litoral area where there are many aquatic plants. This information of nyalian fish could use as the basis for fish resource management in Tamblingan Lake. Abstrak Danau Tamblingan adalah sebuah danau bentukan vulkanisme terletak di kaldera Gunung Lesung dan merupakan danau tadah hujan yang berada di dalam sebuah cekungan endorheic yang terkurung, serta tidak terdapat aliran masuk ataupun aliran keluar danau yang jelas. Nyalian merupakan jenis ikan Famili Cyprinidae yang cukup banyak ditemukan dibandingkan dengan jenis ikan lain di kelasnya di Danau Tamblingan. Informasi parameter pertumbuhan dan persebaran ikan ini di Danau Tamblingan tidak ada. Penelitian ini bertujuan untuk menganalisis dan menjelaskan pola pertumbuhan Barbodes binotatus khususnya hubungan panjang bobot dan faktor kondisi serta persebarannya di perairan Danau Tamblingan. Penelitian dilakukan di Danau Tamblingan kurun waktu Januari – Juni 2019 dengan menggunakan jaring insang yang dimodifikasi dengan ukuran mata jaring 0,5; 1,0; 1,5; 2,0; 2,5; 3,0 cm. Penangkapan ikan dilakukan di lima lokasi. Hubungan panjang bobot dianalisis menggunakan regresi power. Ikan yang ditemukan selama penelitian sebanyak 204 ekor dengan kisaran panjang total 5,2 – 15,0 cm. Persamaan hubungan panjang-bobot ikan adalah W = 0,0051 L3,387. Nilai b yang terbentuk berdasarkan rumus tersebut adalah 3,387 dengan pola pertumbuhan allometrik positif. Nilai faktor kondisi berkisar antara 0,587 – 1,246. Barbodes binotatus menyebar di daerah litoral danau yang banyak tumbuhan air. Informasi terkait ikan nyalian ini dapat digunakan sebagai salah satu dasar dalam pengelolaan sumber daya ikan di Danau Tamblingan.